Scriptorum de Musica Medii Aevi. Novam Seriem a Gerbertina Alteram Tomus I - Coussemaker, Edmond de 1805-1876 (Farnborough A. Durand et Pedone-Lauriel, 1867)
Coussemaker was one of the first to be devoted to research on medieval music and his numerous publications focused on subjects such as the Gregorian chant, the neumatic and measured notation, medieval instruments, and the theory and polyphony he called harmony. What distinguished Coussemaker from Fétis is the wide culture of the latter that enabled him to synthesise huge quantities of information in order to elaborate on abstract theories. De Coussemakers approach is nonetheless more accurate, more scientific and more hypothetical. His Scriptorum de musica, a compilation of writings (most of them in Latin) of several theoreticians of ancient music, is his most important work.
Keywords: 19th Century (1801-1900); Middle Ages (500-1400); Plainchant; Music theory; Notation; Harmony